2012
DOI: 10.1002/jsfa.5900
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between physiological indicators in blood, and their yield, as well as chemical composition of milk obtained from organic dairy cows

Abstract: The study has shown significant correlations between metabolic profiles and milk yields, as well as milk composition. In addition, there is evidence that the intensity of the production system significantly influences the metabolic profile and chemical composition of cow's milk. It could even be concluded that the ecological system affects not only the quality of milk, but also the health of cows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 28 publications
(35 reference statements)
2
42
1
2
Order By: Relevance
“…Pasture quality has a major effect on the performance of grazing animals (Kuczyńska ; Kuczyńska and others ). The quality of the diet of dairy cows in the organic system strongly influences the content and composition of milk protein, fat, and the fat‐soluble micronutrient fraction of dairy products, in particular vitamins A and E (Sakowski and others ). Brodziak and others () reported higher concentrations of Lf and PUFA in milk obtained from cows kept in the traditional system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pasture quality has a major effect on the performance of grazing animals (Kuczyńska ; Kuczyńska and others ). The quality of the diet of dairy cows in the organic system strongly influences the content and composition of milk protein, fat, and the fat‐soluble micronutrient fraction of dairy products, in particular vitamins A and E (Sakowski and others ). Brodziak and others () reported higher concentrations of Lf and PUFA in milk obtained from cows kept in the traditional system.…”
Section: Resultsmentioning
confidence: 99%
“…Many factors affect the FA composition of bovine milk, including season (Sakowski and others ), parity (Puppel and others ), access to fresh grazing (Kuczyńska ; Kuczyńska and others ), grazing sward type (Hauswirth and other ), silage type (Dewhurst and others ), polymorphic forms of β‐lactoglobuline (Puppel and others ) or fish oil, and linseed supplementation (Puppel and others , ). Our study showed that the content of monounsaturated fatty acids (MUFA) in milk fat was dependent largely on the concentration of PUFA, and to a lesser extent on the supply of MUFA (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…High oxidative stress is common in organs and tissues with high metabolic and energy demands, including skeletal and heart muscle, liver and blood cells . Milk composition can be altered by the feeding regime . Antioxidants can be transferred either directly from the feed to the milk, or indirectly, diet supplements cows' milk .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sakowski et al (2012) discuss the effect of breeding on the contents of conjugated linoleic acid (CLA) and lipophilic vitamins. In their experiment, Holstein Friesian dairy cows kept in organic herds gave milk with a higher level of antioxidants.…”
mentioning
confidence: 99%